AB0462 BEHCET'S DISEASE: CLINICAL FEATURES AND OFF-LABEL BIOLOGIC TREATMENT STRATEGIES. (13th June 2020) - Bellis, E.; Monti, S.; Balduzzi, S.; Delvino, P.; Biglia, A.; Montecucco, C.
Abstract : Background: The treatment of Behçet's disease (BD) is still mainly based on the evidence derived from case reports, case series, retrospective analyses, and few clinical trials suggesting the safety and potential efficacy of off-label use of biologic agents in refractory cases. 1 Objectives: To describe clinical manifestations and their management, with particular focus on treatment indications, outcomes and safety of biologic therapy, in a cohort of patients with BD. Methods: Patients with a diagnosis of BD who visited our outpatient clinic until December 2019 were included in the study. Clinical data were recorded since diagnosis until the latest follow-up visit, analyzing clinical features, flares and therapeutic strategies adopted. Results: A total of 95 patients were included in the study with a medium follow-up of 108.54 ± 169.59 months. 20 of them (21. 05%) were treated with biologic agents. Patients treated with biologic therapy compared to those on conventional non-biologic therapies had a higher proportion of musculoskeletal (80% vs 46.67%, p = 0.008), neurological (30% vs 10.67%, p = 0.031), intestinal involvement (40% vs 12%, p = 0.004), and they were treated with a higher dose of glucocorticoids at diagnosis (16.84 mg ±14.01 vs 8.89 mg ± 11.76, p = 0.012). The most frequent indications for biologic step-up therapy were musculoskeletal involvement (40%), eye involvement (25%), neurological involvement (15%) and intestinal involvement (10%). Most patients initiated a biologic treatment within the first year of follow-up. TNF-inhibitor (TNFi) were more frequently prescribed (95%) and one patient was treated with 8 therapeutic cycles of Rituximab (500 mg/weekly for 4 infusions to be repeated after at least 6 months) because of recurrent pancytopenia. All patients experienced non-biologic therapy before starting a TNFi. The preferred first-line TNFi was infliximab (50%), followed by adalimumab (40%) and etanercept (5%). As second line treatment were also prescribed certolizumab (10%) and golimumab (5%). 10 patients switched to a second line treatment because of inefficacy of the first biologic agent, mainly because of refractory arthritis, intestinal and mucocutaneous involvement. One patient switched from infliximab to certolizumab during pregnancy with subsequent worsening of arthritis. 85% of patients treated with biologic agents reached a clinical remission by the time of the latest follow up visit without any safety or tolerability issues. Conclusion: A relevant proportion of patients in our BD cohort were treated with biologic therapy, because of severe or refractory manifestations. The most frequent indications were musculoskeletal, neurological or intestinal involvement. Biologic agents were a generally effective and safe therapeutic approach. References: [1]F. Alibaz-Oner, M. H. Sawalha, H. Direskeneli. Management of Behçet disease, Curr. Opin. Rheumatol, 2018 Disclosure of Interests: None declared